Smart sensing with edge intelligence for autonomous structural health monitoring - Chen, John Yong Han (Nanyang Technological University, 2023)
In the pursuit of Singapore becoming a Smart Nation, the integration of advanced technologies, such as sensors in structural health monitoring systems, has become paramount. This paper delves into the significance of sensor reliability in these monitoring systems. Sensor malfunctions, largely attributed to external environmental factors and internal hardware issues, compromise the reliability of these systems. With this in mind, this study aims to develop an Artificial Intelligence (AI) framework that integrates edge computing, distributed learning, and structural health monitoring with sensor fault diagnosis.